Lead-doped cubic tin sulfide thin films for solar cell applications. (1st November 2022) - Chalapathi, U.; Jayasree, Y.; Park, Si-Hyun
Abstract: Cubic tin sulfide (SnS), an earth-abundant and non-toxic material, is a promising candidate for thin film solar cells. Lead(Pb)-doped (0.0–11.6 atomic percent (at.%)) cubic SnS thin films were prepared via chemical bath deposition to achieve improved structural, optical, and electrical properties. X-ray diffraction studies revealed that the films were polycrystalline and exhibited cubic crystal structure, decreased crystallite size, and increased lattice parameter, strain, and dislocation density on increasing Pb content. Field emission scanning electron microscopy images revealed increased grain size up to 2.5 at.% and decreased grain size beyond 2.5 at.% of Pb content. Optical absorption studies showed a decrease in the band gap from 1.73 to 1.64 eV upon increasing the Pb dopant concentration. Hall measurements revealed an increase in the hole mobility up to 2.5 at.% and decreased mobility beyond the 2.5 at.% of Pb dopant concentration. In conclusion, the prepared cubic SnS films have potential for application in solar cells because of the demonstrated reduced optical band gap and enhanced hole mobility resulting from Pb-doping.